Dermatologic reactions in cancer therapies - Fabbrocini, Gabriella; Lacouture, Mario E.; Tosti, A. (Antonella) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
Chemotherapy and radiotherapy for cancer can have devastating side effects on the skin of a patient. This innovative guide for both dermatologists and oncologists gives a good introduction both to therapy regimes and to dermatological management for medical professionals treating their patients.
Introduction to anticancer therapies / Jennifer Wu and Mario E. Lacouture -- Acneiform eruptions / Gabriella Fabbrocini, Maria Concetta Romano, Sara Cacciapuoti, and Luiga Panariello -- Hair disorders / Azael Freites-Martinez, Gabriella Fabbrocini, Mario E Lacouture, and Antonella Tosti -- Photosensitivity and photo-reactions / Cecilia A. Larocca, Mackenzie Asel, and Mario E. Lacouture -- Hyperkeratotic reactions / Vincent Sibaud and Maria Vastarella -- Sclerotic eruptions / Bernice Y Kwong -- Hand foot reactions / Mathew R. Birnbaum, Loren G. Franco, and Beth N. McLellan -- Oral mucosal reactions to anticancer therapies / Emmanuelle Vigarios and Vincent Sibaud -- Chemotherapeutic-induced nail reactions / Eric Wong, Maria Carmela Annunziata, and Antonella Tosti -- Neoplastic reactions / Peter Arne Gerber -- Hypersensitivity and urticaria / Cataldo Patruno, Maria Ferrillo, and Maria Vastarella -- Xerosis, itching, and fissures / Gabriella Fabbrocini, Tiziana Peduto, and Mariateresa Cantelli -- Radiation dermatitis / John D Strickley and Jae Jung.
OCLC-licensed vendor bibliographic record.
Keywords: Cancer -- Treatment; Cancer -- Complications; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; MEDICAL / General; MEDICAL / Dermatology; MEDICAL / Family & General Practice